Attenuation of renovascular damage in zucker diabetic fatty rat by NWT-03, an egg protein hydrolysate with ACE- and DPP4-Inhibitory activity - Wang, Yumei; Landheer, Sjoerd; Hammes, Hans-Peter (PLOS ONE, 2012)
Background Dipeptidyl peptidase 4 (DPP4) and angiotensin-converting enzyme (ACE) are important target enzymes in glycemic control and renovascular protection. Here, we studied the effect of NWT-03, an egg protein hydrolysate with DPP4- and ACE-inhibitory activity, on renovascular damage in Zucker diabetic fatty (ZDF) rats. Comparisons were made to rats treated with vildagliptin (VIL), included as a positive control for the effect of DPP4 inhibition. Methods ZDF rats received NWT-03 (1 g/kg/day) or VIL (3 mg/kg/day) from 10 to 25 weeks of age. Metabolic and renal functions were assessed; the kidney was removed for histological analysis of glomerulosclerosis and expression of pro-inflammatory/fibrotic markers (RT-PCR and Western blotting); and the aorta was removed for studies of endothelium-dependent relaxation (EDR). Findings Hyperinsulinemic ZDF rats typically developed signs of type-2 diabetes and renovascular damage, as evidenced by albuminuria, glomerulosclerosis, and impaired EDR. Neither NWT-03 nor VIL improved metabolic parameters; for VIL, this was despite a 5-fold increase in glucagon-like peptide (GLP)-1 levels. NWT-03 and VIL both reduced renal interleukin (Il)-1β/Il-13 mRNA expression and glomerulosclerosis. However, only NWT-03 additionally decreased renal tumor necrosis factor (TNF)-α mRNA and P22phox protein expression, reduced albuminuria, and restored aortic EDR. Indomethacin added to the organ bath instantly improved aortic EDR, indicating a role for cyclooxygenase (COX)-derived contractile prostanoids in opposing relaxation in ZDF rats. This indomethacin effect was reduced by NWT-03, but not by VIL, and coincided with decreased renal COX-1/2 protein expression. Conclusion and Interpretation Long-term supplementation with the egg protein hydrolysate NWT-03 attenuated renovascular damage in this preclinical rat model of type 2 diabetes. A comparison to the DPP4-inhibitor VIL suggests that the effects of NWT-03 were related to both ACE- and DPP4-inhibitory properties. The development of protein hydrolysates with a multiple-targeting strategy may be of benefit to functional food formulations.
Gesehen am 26.02.2019